Analysis of Price Perception, Service Quality, and Product Quality on Pur-chase Decisions at Mie Gacoan - Gultom, Masrina; Asri, Wulandari; Nirmala, Yanti (Institute for Law and Economics Studies, 2025)
This research aims to analyze the influence of price perception, service quality, and product quality on the purchasing decision of Mie Gacoan. The method used includes data collection through questionnaires distributed to Mie Gacoan consumers, focusing on the variables consid-ered to influence purchasing decisions. The analysis results show that product quality and service quality have a significant positive impact on purchasing decisions, while price perception has a negative and insignificant effect. The combined contribution of these three variables explains about 65.37% of the variation in purchasing decisions, indicating that these factors are highly relevant in determining consumer choices. These findings provide important insights for Mie Gacoan's